Eksplorasi Pengalaman Siswa dalam Project Based Learning Berbasis Microsite: Studi Fenomenologi Literasi Ekologi di Sekolah Dasar: Eksplorasi Pengalaman Siswa dalam Project Based Learning Berbasis Microsite: Studi Fenomenologi Literasi Ekologi di Sekolah Dasar - Dian Rohmani, Dian Rohmani; Riska Pristiani; Oktaviani Adhi Suciptaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This phenomenological qualitative study explores elementary students' subjective experiences in Project-Based Learning (PjBL) using microsites to enhance ecological literacy. Despite technological advancements in education, conventional methods often fail to foster comprehensive ecological awareness due to teacher-centered approaches and limited media (Ernst & Monroe, 2022). This research addresses this gap by investigating how microsite-based PjBL shapes students' environmental consciousness through interactive, contextual learning (Hernández-Ramos & De La Paz, 2021). The study involved 28 fourth-grade students from Malang, Indonesia, who participated in a four-week microsite project integrating multimedia content (videos, infographics) and collaborative activities. Data were collected through semi-structured interviews (10 students), participatory observations (6 sessions), and document analysis (digital posters, daily reflections), then analyzed using van Manen’s (2022) phenomenological approach to identify essential themes. Three key findings emerged: (1) Microsites as Interactive Exploration Spaces: 78.6% of students (22/28) reported that multimedia features facilitated autonomous learning, though 5 initially faced technical challenges; (2) Digital Collaboration and Emotional Engagement: 65% (18/28) felt motivated by collaborative features (e.g., comment sections), while 7 students experienced initial discomfort with digital interaction; and (3) Contextual Learning and Ecological Transformation: 19 students adopted pro-environmental behaviors (e.g., reducing plastic use), supported by 85.7% of reflections (24/28) showing heightened environmental awareness. The study highlights microsites’ role as